Defending the Masses : A Progressive Lawyer's Battles for Free Speech - Easton, Eric B. (Book collections on Project MUSE., 2018)
"As muckrakers, feminists, pacifists, anarchists, socialists, and communists were arrested or censored for their outspoken views, many of them turned to a Manhattan lawyer named Gilbert Roe to keep them in business and out of jail. In articulating and upholding Americans' fundamental right to free expression against charges of obscenity, libel, espionage, sedition, or conspiracy during turbulent times, Roe was rarely successful in the courts. His greatest victory was the influential 1917 decision by Judge Learned Hand in 'The Masses Publishing Co. v. Patten'. Roe's battles illuminate the evolution of free speech doctrine and practice in an era when it was under heavy assault."--Back cover